Optimization or two matching layers for the wide-band transducer - WESOŁOWSKI, Z. (Archives of Acoustics, 1994)
Two homogeneous elastic layers are situated between two homogeneous elastic materials. If the harmonic wave propagates in the direction perpendicular to the layers, then the reflection coefficient depends on the elastic constants of the layers, their thickness and frequency. If, instead of the monochromatic wave, the pulse is propagating, then the reflection coefficient depends on the frequency spectrum. The pulse in the form of two or four periods of the sine curve is considered. It is decomposed into a sum, of harmonic, monochromatic waves. In calculations the pulse was assumed to be a sum of 22 harmonic waves of different frequencies. The reflection coefficient for this sum was determined. The reflection coefficient possesses several minima. Only two of them are technially interesting. For one of them the thicknesses of the two layers are of the same order.